Analyzing Startup Financing Models In Indonesia: A Bibliometric Study - Elwisam; Digdowiseiso , Kumba; Yartono , Nungki (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research uses bibliometric analysis to investigate research developments related to startup financing models in Indonesia from 2016 to 2023. Bibliographic data was obtained through Semantic Scholar with the key term "Startup Financing Models in Indonesia." Quantitative analysis and VosViewer software are used to identify publication patterns, research growth, and contributions of leading authors, journals, and institutions. The results show variations in researcher interest from year to year, with a significant increase in 2020 but a sharp decrease in 2022-2023. Co-citation and co-authorship analysis helps identify relationships between researchers, articles, and concepts that are frequently mentioned together. Knowledge mapping via VosViewer produces four main clusters: startups, MSMEs, financing, and data; quantitative approach and secondary data; returns, assets, and ROA; as well as funds and financing that perform well. The overlay and density visualization of research themes shows changes in terms over time and identifies themes that have not been widely explored.